Gambaran Kepuasan Pengguna Aplikasi Mobile JKN Dengan Metode Analisis E-Servqual - Meila Nissa Solihah; Winda Azmi Meisari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
This research was conducted to determine the level of service quality of the Mobile JKN application using the 7 dimensions of e-ServQual. Measuring service quality is done by calculating the gap between the expected service and the service received by customers. The main data was collected using a questionnaire that had passed validity and reliability tests using the Statistical Program for Social Science (SPSS) software. The questionnaire was filled in by respondents who had registered and used the Mobile JKN application using primary data collection techniques with a sample size of 100 people rounded up to 102 respondents. And from the results of the research conducted it can be concluded that based on the analysis of the gap values ​​in each e-ServQual dimension for the Mobile JKN application, it was found that all dimensions have negative gap values, the efficiency dimension has a gap of -0.167 in the reliability dimension (reliability) has a gap of -0.093, the fulfillment dimension has a gap of -0.005, the privacy dimension has a gap of -0.059, the responsiveness dimension has the largest gap, -0.176, the compensation dimension has a gap of -0.118 , finally the contact dimension has a gap of -0.172.